Inventory Analysis of Packed Red Cells Components Using Monte Carlo Simulation - Fasyabib, Fachrul Yazid; Qisthani, Nabila Noor; Kasanah, Yulinda Uswatun (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2025)
This study analyzes Packed Red Cells (PRC) inventory management at PMI Banyumas using a Monte Carlo simulation to evaluate different stock management strategies. The initial model shows a significant shortage of blood supply. Two alternative scenarios were simulated to address this issue: adding 55 additional units from external sources and increasing donor participation by 15%. The simulation results demonstrate that these strategies effectively reduce the shortage from 62 units to just 5 units without increasing expired inventory while achieving the lowest total cost of Rp. 9,927,682. These findings highlight that increasing donor participation offers the best performance in balancing supply and demand. This study provides simulation-based strategic recommendations that other PMI branches can replicate to improve bloodstock management, reduce shortages, and maintain optimal service levels.